COMPARISON OF ARECA CATECHU L. EXTRACT AND ETHANOL EXTRACT PIPER BETLE L. IN DECREASING BLEEDING TIME POST TOOTH EXTRACTION - Bella Fernanda; Welly Effendy Seba; Suci Erawati (Jurnal Penelitian Pendidikan IPA, 2024)
Tooth extraction is one of the simple procedures commonly found in dentistry. Bleeding is a common complication following this procedure. It requires special equipment and can quickly lead to shock, syncope, and death if not treated promptly. This study aimed to determine the effectiveness of Areca seed or beetle leaf ethanol extract in shortening bleeding time after tooth extraction in a Wistar rat model. Thirty-two male Wistar rats were divided into two treatment groups. The first group was treated with piper beetle leaf ethanol extract, and the second group was treated with areca seed ethanol extract. This extract was directly applied to the tooth socket. Meanwhile, the bleeding time was recorded on a filter paper every half minute using a stopwatch. All data were analyzed by T-Independent Test. The results of this study indicated a significant difference in bleeding time between the first group (betel leaf ethanol extract) and the second group (areca seed ethanol extract) with a p-value < 0.001. The mean bleeding time for the first group (143.19 ± 15.93 seconds) was longer than that for the second group (88.06 ± 23.80 seconds). Overall, it can be concluded that the areca seed ethanol extract significantly shortens bleeding time compared to piper beetle extract.